The Role of Parents in Overcoming Adolescent Moral Crisis In Wairbleler Village, Waigete District, Sikka Regency - Mahmud, Syafriansah; Kasim, Abdul Muis; Nuwa, Gisela (Lembaga Riset Mutiara Akbar, 2023)
The role of parents is one of the roles not only as the head of the family, earning a living but the function of parents is also to educate, by instilling moral values, and parents exemplify positive behavior to adolescents. Good citizens must have good citizenship in the formation of positive young people's behavior, starting from the family implementing the religious guidance of parents in dealing with the moral crisis of adolescents.